THE INFLUENCE OF GREEN MARKETING, BRAND IMAGE, AND THE PRODUCT QUALITY TOWARDS CUSTOMER SATISFACTION OF THE BODY SHOP, MANADO TOWN SQUARE - Wenur, Christy; Mandey, Silvya; Tumbuan, Willem A. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Global warming is a serious problem that is being faced by people around the world. However, global warming is viewed as a specific business opportunity for certain companies. Green marketing strategy is one of the solutions to deal with this business opportunity, especially for companies in the field of cosmetics. The Body Shop is an international cosmetic product retailer that already have a good image and quality while still promoties green marketing strategy. The research objective is to determine the effect of  green marketing strategy, brand  image and product quality both simultaneously and partially on customer satisfaction as  Body Shop Manado Town Square’s consumers. The sample used in this study amounted to 100 people. The analysis method was used  multiple linear regression analysis. The results shows that green marketing strategy, brand  image and product quality simultaneously  influence  satisfaction. Partially, green marketing strategy, and product quality significantly influences  consumer satisfaction,  while brand image  partially does not  significantly influence  customer satisfaction. The Body Shop Manado Town Square should take into account the Green Marketing Strategy, brand image and product quality and  to continuously selling  products that are environmentally  friendly and can be recycled because those  product quality are expected by the consumers. Keywords: marketing strategy, brand image, product quality, consumer satisfaction